Structures and Stabilities of (MgO) n Nanoclusters - Chen, Mingyang; Felmy, Andrew R; Dixon, David A (The journal of physical chemistry. A, Molecules, spectroscopy, kinetics, environment, & general theory, 2014)
Global minima for (MgO) n structures were optimized using a tree growth–hybrid genetic algorithm in conjunction with MNDO/MNDO/d semiempirical molecular orbital calculations followed by density functional theory geometry optimizations with the B3LYP functional. New lowest energy isomers were found for a number of (MgO) n clusters. The most stable isomers for (MgO) n (n > 3) are 3-dimensional. For n < 20, hexagonal tubular (MgO) n structures are more favored in energy than the cubic structures. The cubic structures and their variations dominate after n = 20. For the cubic isomers, increasing the size of the cluster in any dimension improves the stability. The effectiveness of increasing the size of the cluster in a specific dimension to improve stability diminishes as the size in that dimension increases. For cubic structures of the same size, the most compact cubic structure is expected to be the more stable cubic structure. The average Mg–O bond distance and coordination number both increase as n increases. The calculated average Mg–O bond distance is 2.055 Å at n = 40, slightly smaller than the bulk value of 2.104 Å. The average coordination number is predicted to be 4.6 for the lowest energy (MgO)40 as compared to the bulk value of 6. As n increases, the normalized clustering energy ΔE(n) for the (MgO) n increases and the slope of the ΔE(n) vs n curve decreases. The value of ΔE(40) is predicted to be 150 kcal/mol, as compared to the bulk value ΔE(∞) = 176 kcal/mol. The electronic properties of the clusters are presented and the reactive sites are predicted to be at the corners.